Sunflower seed hull based compost for Agaricus blazei Murrill cultivation - Gonzalez Matute, Ramiro (2010)
Agaricus blazei Murrill is actually one of the most promising mushrooms species. An adaptation from the traditional biphasic compost fermentation method for Agaricus bisporus cultivation has been used for its cultivation. To make mushroom production profitable, the selection of compost materials from each region is essential. Sunflower seed hulls are an abundant lignocellulosic waste from the edible oil industry. It has been successfully used in the cultivation of other specialty mushrooms; however, there are no published reports on its use as part of Agaricus spp. compost. There is still no agreement about the usage of lignin by A. bisporus, and in the case of A. blazei there is no published data. This work presents a substrate formulation (50.0% sunflower seed hulls, 41.0% wheat straw, 4.5% wheat bran, supplements and additives) which after composting was assayed to evaluate the performance of A. blazei cultivation. Different types of containers, i.e. polyethylene bags (2.5 and 4.0 kg substrate, 0.08 m2 ) and plastic trays (3.5 and 4.5 kg substrate, 0.12 m2 ), in two independent trials, were also evaluated. It was demonstrated that the obtained compost was appropriate for the cultivation of A. blazei yielding BE ranging from 30% to 47%, depending on the container and substrate mass, being highest with polyethylene bags containing 2.5 kg substrate. In this case study, lignin accumulated during the composting process, but an important reduction was observed during the cultivation (58% on average), confirming the ability of this mushroom to degrade lignin; thus making it possible the access to nutrient sources of cellulose and hemicellulose.